2017
DOI: 10.1111/jzo.12509
|View full text |Cite
|
Sign up to set email alerts
|

Gaining insights into in situ behaviour of an endangered seahorse using action cameras

Abstract: Observation bias is an Achilles heel of behavioural research, particularly during underwater in situ assessments. The advent of small, affordable underwater action cameras has helped to overcome this problem and were used to investigate the behaviour of the endangered Knysna seahorse (Hippocampus capensis) within a South African residential marina estate during the austral summer. Four GoPro® cameras were deployed over three time periods, October to December 2015, December 2015 to January 2016 and January to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…and this results in a marked increase in boat use within the canals and the estuary. When exposed to loud noise, H. erectus exhibited physiological, chronic stress responses with reduced mass and body condition (Anderson et al ., ) and it is possible that the increase in boat noise during the summer holiday period played a role in decreased population densities (Claassens & Hodgson, ). Further research on the potential effect of increased noise on H. capensis caused by boat activity is required.…”
Section: Discussionmentioning
confidence: 99%
“…and this results in a marked increase in boat use within the canals and the estuary. When exposed to loud noise, H. erectus exhibited physiological, chronic stress responses with reduced mass and body condition (Anderson et al ., ) and it is possible that the increase in boat noise during the summer holiday period played a role in decreased population densities (Claassens & Hodgson, ). Further research on the potential effect of increased noise on H. capensis caused by boat activity is required.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown from the open population estimates that the probability of resighting marked individuals decreased over time and was particularly low for the months of November–December. Past research found a comparable decrease in H. capensis numbers and sightability during December 2015 (Claassens & Hodgson, 2018b) which was suggested to be owing to an increase in boat noise during the summer holiday period. As this study was focused on a site located within a residential marina estate, regular maintenance activities take place.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, different sampling approaches can significantly affect recapture rates; for example, recapture rates for H. zosterae increased from 0.47% to 33% by changing the sampling resolution (Masonjones et al, 2019). This study used closed population surveys to allow (Claassens & Hodgson, 2018b) which was suggested to be owing to an increase in boat noise during the summer holiday period. As this study was focused on a site located within a residential marina estate, regular maintenance activities take place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harvey et al, 2001, Jaquet, 2006, behavioural studies (e.g. Nguyen et al, 2014, Claassens andHodgson, 2018) and in aquaculture (e.g. Costa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%